Les modes de conceptualisation des unités d’hérédité au XIXe siècle : Spencer, Haeckel et Elsberg - Vandaele, Sylvie; Béland, Marie-Claude (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Ever since the end of the 19th century, the biological sciences have been preoccupied with the elucidation of the complex mechanisms underlying heredity. They were faced with a fundamental problem: how does a given phenotypic trait (e.g., skin or fur color) correspond to a physical entity, more often than not putative, responsible for its transmission from one generation to the next. The discovery and subsequent characterization of the unit of inheritance (unité d’hérédité) is thus the central focus of research on heredity in many fields, namely genetics, population genetics, molecular biology, and, more recently, genomics. What we now call gene since Johanssen coined the term, however, has a long and troubled past characterized by various successive conceptualizations. These have left sometimes confusing and even contradictory features in modern scientific discourse, of which we intend to understand the origins. The present article aims to examine the different embodiments of the concept unit of inheritance in the works of two key 19th century authors: Spencer and Haeckel. Elsberg, a rival of Haeckel, will also be considered. Using an analysis of indices of conceptualization in discourse, we show the various metaphorical conceptualization modes active in their respective theories and examine how they manifest themselves in English and in French.